2013
DOI: 10.1523/jneurosci.1506-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Plant Sterols the Better Cholesterol in Alzheimer's Disease? A Mechanistical Study

Abstract: Amyloid-␤ (A␤), major constituent of senile plaques in Alzheimer's disease (AD), is generated by proteolytic processing of the amyloid precursor protein (APP) by ␤-and ␥-secretase. Several lipids, especially cholesterol, are associated with AD. Phytosterols are naturally occurring cholesterol plant equivalents, recently been shown to cross the blood-brain-barrier accumulating in brain. Here, we investigated the effect of the most nutritional prevalent phytosterols and cholesterol on APP processing. In general,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(74 citation statements)
references
References 76 publications
1
71
0
Order By: Relevance
“…In fact, stigmasterol demonstrated anti-amyloidogenic properties, decreased ␤-secretase cleavage of APP, and decreased A␤ generation. Moreover, mice fed stigmasterol-enriched diets showed decreased ␥-secretase complex protein expression but lacked direct inhibition of ␥-secretase activity in isolated mouse brain tissue (32). We also observed that cyclopamine treatment decreases ␥-secretase-mediated proteolysis of APP without inhibiting ␥-secretase activity directly.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In fact, stigmasterol demonstrated anti-amyloidogenic properties, decreased ␤-secretase cleavage of APP, and decreased A␤ generation. Moreover, mice fed stigmasterol-enriched diets showed decreased ␥-secretase complex protein expression but lacked direct inhibition of ␥-secretase activity in isolated mouse brain tissue (32). We also observed that cyclopamine treatment decreases ␥-secretase-mediated proteolysis of APP without inhibiting ␥-secretase activity directly.…”
Section: Discussionmentioning
confidence: 55%
“…Phytosterols were recently shown to modify APP metabolism. Some phytosterols increased amyloidogenic processing and A␤ levels, and others decreased A␤ levels (32). In fact, stigmasterol demonstrated anti-amyloidogenic properties, decreased ␤-secretase cleavage of APP, and decreased A␤ generation.…”
Section: Discussionmentioning
confidence: 95%
“…Beside the fact that APP itself and its processing secretases are all transmembrane proteins, amyloidogenic APP processing is discussed to be dependent on particular membrane microdomains, called lipid rafts, enriched in cholesterol and sphingolipids [5]. Furthermore, several lipids have been shown to alter Aβ generation, including gangliosides, sphingomyelin, trans -fatty acids, phytosterols, cholesterol and docosahexaenoic acid (DHA) [6,7,8,9,10,11,12]. DHA, an ω-3 polyunsaturated fatty acid (PUFA) predominantly found in marine fish and algae, was shown to reduce Aβ production in vitro and in animal models of AD [12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Phytosterols should be consumed (1-2 g/day) and excessive intake of phytosterols leads to neurotoxicity with neurodegeneration [37]. Phytosterols cross the blood-brain barrier in neurons to maintain neuron amyloid beta homeostasis [161]. Consumption of plant-based foods essential for phytosterol ingestion should be assessed for caffeine content since approximately 40 caffeine containing plants have been reported.…”
Section: Nutritional Diets Maintain Brain and Adipose Tissue-liver Crmentioning
confidence: 99%